(untitled) (Research, Society and Development, 2022)
Protein synthesis is an essential topic for the understanding of other subjects in the field of Biology, but teachers and students still struggle with it, since it involves submicroscopic, and molecular concepts and processes. Nowadays, due to technological advancement and easy internet access, multimedia presents itself as a meaningful resource that can be a tool for learning. This study’s objective was to analyze video lessons about protein synthesis, available on YouTube, through the perspectives of the Cognitive Theory of Multimedia Learning (CTML). The method of analysis was qualitative through the submission of the nine most viewed video lessons on protein synthesis available on YouTube to eleven principles of the CTML. We noted deviations in the principles of coherence, pre-training, and image as the most recurrent in the video lessons. It is important to plan the development of multimedia resources considering some theoretical and methodological input, thus avoiding obstacles in the teaching-learning process.